Microsatellite Analysis of Expressed Sequence Tags and Development of EST-SSR Markers for Melampsora spp - Zhibing, Wan; Min, Liu; Wanxu, Yang; Xinye, Zhang; Tongming, Yin (Plant Diseases and Pests(植物病虫害研究：英文版), 2013)
In this study,64 498 ESTs of Melampsoraspp.was assembled into 1 998 contigs,and 604SSR loci were detected on these contigs,with 736.6 bp containing one SSR on average.Among these SSRs,trinucleotide repeats were the most abundant repeats（44.70%）.As for the composition of microsatellites, AC and AT repeats were the richest motif in dinucleotide repeats,and AGT and AAG repeats were the most frequent motifs in trinucleotide repeats,whereas（AAAN） n and（AAAAN） n repeats were dominant in tetranucleotide and pentanucleotide repeats,respectively.All the dominant repeat motifs of different types of SSRs were rich in A and T.In EST sequences of Melampsoraspp.genome,microsatellites longer than 20 bp accounted for about 15.07%.It was noticeable that microsatellites were highly rich in the expressed sequences of Melampsoraspp.genome,which implied that SSRs played a significant role in triggering the gene mutation in Melampsoraspp.genome.A total of 455 SSR primers were designed according to the detected microsatellites using Primer 5.0 and Oligo 6. 0,and 30 primer pairs were randomly selected for amplification test.Among these primer pairs,27 primer pairs succeed in amplification,with a successful rate of 90%.Eight primer pairs generated polymorphic fingerprints in Melampsoraspp.collected from different poplar genotypes,accounting for 26.7% of the total primer pairs.The EST-SSR markers developed fromMelampsoraspp.EST sequences provided important marker resources for studying Melampsoraspp.from the aspects of pathogen identification and survey of genetic variation.